Meteor Showers An Annotated Catalog - Kronk, Gary W.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
Meteor showers are among the most spectacular celestial events that may be observed by the naked eye, and have been the object of fascination throughout human history. In (3z(BMeteor Showers: An Annotated Catalog,(3y (Bthe interested observer can access detailed research on over 100 annual and periodic meteor streams in order to capitalize on these majestic spectacles. Each meteor shower entry includes details of their discovery, important observations and orbits, and gives a full picture of duration, location in the sky, and expected hourly rates. Armed with a fuller understanding, the amateur observer can better view and appreciate the shower of their choice. The original book, published in 1988, has been updated with over 25 years of research in this new and improved edition. Almost every meteor shower study is expanded, with some original minor showers being dropped while new ones are added. The book also includes breakthroughs in the study of meteor showers, such as accurate predictions of outbursts as well as comet and meteor observations from the 6th century to the 17th century that were not published in the first edition. It holds all of the information needed to inspire a new observer or provide deeper knowledge to the long-time enthusiast.s
January Meteor Showers -- February Meteor Showers -- March Meteor Showers -- April Meteor Showers -- May Meteor Showers -- June Meteor Showers -- July Meteor Showers -- August Meteor Showers -- September Meteor Showers -- October Meteor Showers -- November Meteor Showers -- December Meteor Showers.
Keywords: Physics; Astrophysics; Astronomy; Physics; Astronomy, Observations and Techniques; Popular Science in Astronomy; Atmospheric Sciences; Extraterrestrial Physics, Space Sciences